The Revitalization of Moral Education through a Habituation Approach Grounded in School Culture - Nita Erlina; Ulfa Adilla; Baili; Joni Juli Yandra; Noviriani Noviriani; Sugeng Kurniawan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
Moral education in Islamic junior secondary schools faces several structural challenges, including the dominance of cognitive-oriented approaches, the fragmentation of values in school practices, and the influence of the digital ecosystem, which has shifted the process of character internalization. This study aims to analyze the revitalization of moral education through a school culture-based habituation approach at MTs Tahfizul Quran Rantau Duku, Bungo Regency, Jambi Province. The research employed a qualitative approach with a single-case study design. Data were collected through three months of participant observation, in-depth interviews with 18 informants (the school principal, Islamic Religious Education and moral education teachers, students, parents, and dormitory supervisors), and documentation of school programs. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while source and method triangulation were employed to ensure data trustworthiness. The findings indicate that the revitalization of moral education was developed through three main mechanisms: (1) the construction of a school culture institutionalized through daily routines, codes of conduct, and teacher role modeling; (2) a habituation process following the cycle of modeling, guided practice, independent habituation, and reflective internalization; and (3) the integration of the Tahfiz al-Qur’an program as a medium for strengthening moral conduct and spirituality. Consistent habituation within a supportive school culture ecosystem was found to be effective in internalizing akhlaq al-karimah (noble character), reducing negative behaviors, and enhancing students’ social responsibility. The study concludes that a school culture-based habituation approach represents a holistic, contextual, and sustainable model for revitalizing moral education. Recommendations include strengthening teachers’ capacity building, developing authentic moral assessment instruments, and fostering synergy among schools, families, and communities.